THE CONTEXT OF FIELDWORK PRACTICES IN COMPUTER AND NETWORKING ENGINEERING MAJOR AT VOCATIONAL SCHOOL - Erika Agustariansyah; Yuliatri Sastrawijaya; Lipur Sugiyanta (AL-ISHLAH: Jurnal Pendidikan, 2020)
Field Work Practice is a mandatory program that must be implemented for the delivery of vocational level education or Vocational High Schools. The purpose of this study was to get a more in-depth quality of the context of Fieldwork Practices in the Computer and Network Engineering major at SMK Negeri 3 Oku. This is intended to make understanding of the context clearer. The research method used descriptive qualitative research. The data collection method used interviews, observations, documentation, and questionnaires. The data analysis technique used three stages, namely data reduction, data presentation, discussion, and drawing conclusions. The findings concluded that the context aspect for legality is in accordance with the standard rules for implementing Fieldwork Practices from the government as set forth in the rules and procedures for issuing Fieldwork Practices. Whereas aspects of the characteristics of schools implementing Fieldwork Practices are adjusted to operational standards set by schools and industry. In the context aspects of the needs of the industrial has also been built in accordance with an agreement from the industry. The results of this study also recommend that SMK Negeri 3 Oku continue to increase the amount of collaboration with industry and increase the competence of students and supervisors.